2020
DOI: 10.20944/preprints202009.0339.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between Psychological Factors and Evacuation Status and the Incidence of Cardiovascular Diseases after the Great East Japan Earthquake: A Prospective Study of the Fukushima Health Management Survey

Abstract: Evidence regarding the effect of psychological factors and evacuation on cardiovascular disease occurrence after large-scale disasters is limited. This prospective study followed up a total of 37,810 Japanese men and women aged 30–89 years from the Fukushima Prefecture with no history of stroke or heart disease at baseline (2012), until 2017. This period included 3000 cardiovascular events recorded through questionnaires and death certificates. The participants’ psychological distress, trau… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…18 In addition, psychological distress and trauma reactions were found to increase the risk of new cases of stroke and heart disease after the disaster. 19 It has been well-reported that excessive alcohol drinking causes an increase in A c c e p t e d V e r s i o n blood pressure, 20,21 and hypertension is significantly associated with cardiovascular disease (CVD). 22,23 Based on these findings, we hypothesized that after the disaster, the proportion of excessive drinkers would increase, especially in the evacuation areas, and that excessive drinking would be a risk for an increased incidence of hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…18 In addition, psychological distress and trauma reactions were found to increase the risk of new cases of stroke and heart disease after the disaster. 19 It has been well-reported that excessive alcohol drinking causes an increase in A c c e p t e d V e r s i o n blood pressure, 20,21 and hypertension is significantly associated with cardiovascular disease (CVD). 22,23 Based on these findings, we hypothesized that after the disaster, the proportion of excessive drinkers would increase, especially in the evacuation areas, and that excessive drinking would be a risk for an increased incidence of hypertension.…”
Section: Introductionmentioning
confidence: 99%